Retrospective Study on Bacteria Causing Ventilator-Associated Pneumonia and The Antibiotic Susceptibility Patterns in Intensive Care Unit Patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Nathania Gwendy Indarmastuti; Eko Budi Koendhori; Bambang Pujo Semedi; Rebekah Juniati Setiabudi; Etty Fitria Ruliatna (Majalah Biomorfologi, 2026)
Background: Ventilator-associated pneumonia (VAP) remains one of the most significant nosocomial infections in many critical care patients worldwide. Specifically, it is a pulmonary infection occurring more than 48 hours after endotracheal intubation. Identifying causal pathogens and mapping their antibiotic susceptibility using recent data is essential to support infection control efforts through empirical therapy. Objective: This study aimed to analyze the bacterial species causing VAP and their antibiotic susceptibility patterns (antibiogram) among intensive care unit (ICU) patients at Dr Soetomo General Academic Hospital, Surabaya, Indonesia. Materials and Methods: This study used a retrospective cross-sectional design. The study population comprised ICU patients diagnosed with VAP between January 2023 and December 2024. The study also collected data on patients’ bronchoalveolar lavage (BAL) and/or endotracheal aspirate (ETA) culture results and antibiotic susceptibility tests. The collected data were subsequently analyzed using descriptive statistical methods to identify the frequency of pathogens and the percentage of antibiotic sensitivity. Results: A total of 26 positive BAL/ETA culture isolates were found, with the most common causative bacteria of VAP being gram-negative species, predominantly Pseudomonas aeruginosa (42.31%), Acinetobacter baumannii (19.23%), and Enterobacter cloacae (15.38%). Gram-negative bacteria demonstrated the highest susceptibility to amikacin (AK) and cefoperazone–sulbactam (SCF). Conclusion: Predominant pathogens causing VAP were Gram-negative bacteria, particularly Pseudomonas aeruginosa. AK and SCF may be considered empirical options based on the local ICU antibiogram. Regular updates on ICU antibiograms and adequate nosocomial infection control through preventive measures are crucial in preventing VAP.